Factors influencing job retention and satisfaction among nurses in tertiary level hospital - Rana, Mana Maya; Shakya, Nona (Journal of Gandaki Medical College-Nepal, 2021)
Introduction: Retention of nurses in any health care facilities is essential for maintaining quality nursing care. Nurses’ job satisfaction is an important issue to retain nurse in same organization. The study aimed to assess factors influencing job retention and satisfaction among nurses.Methods: The descriptive cross-sectional study was done among 125 nurses working in Manipal Teaching Hospital. Purposive sampling technique was used to select the sample. The semi structured self-administered questionnaire was used to collect data. The collected data was analysed by using descriptive and inferential statistic.Results: Majority (90.4%) of nurses were in age group 21 to 39 years, 78.4% of nurses wanted to continue their job in current organization. All the nurses agreed on timely payment of salary followed by good working relationship with colleagues (93.6%), feeling proud to tell name of organization (89.6%), adequate supplies and equipment (83.2%), safe working environment (80.6%), opportunity to develop many job skill (81.6%), supportive matron (75.2%), the financial incentives such as bonus and allowance (67.2%), higher salary compared to similar organization (64.8%) are important factors to motivate nurses to retain in current organization. Only half of the nurses (50.4%) were satisfied with their job. The significant correlation was seen between factors influencing job retention and their satisfaction level.Conclusion: The study concluded that timely payment of salary, image of organization, safe working environment and adequate equipment and supplies are important factors to retain in this organization.